2021
DOI: 10.1111/1759-7714.14183
|View full text |Cite
|
Sign up to set email alerts
|

Response and safety of whole‐brain radiotherapy plus temozolomide for patients with brain metastases of non‐small‐cell lung cancer: A meta‐analysis

Abstract: The aim of the present work was to investigate the response and safety of whole-brain radiotherapy (WBRT) plus temozolomide (TMZ) for patients with brain metastases of non-small-cell lung cancer (NSCLC). Methods: The electronic databases of Pubmed, EMbase, Cochrane, Wangfang, china national knowledge infrastructure (CNKI), and Google scholar were systematically searched to identify the prospective randomized trials relevant to WBRT plus TMZ for patients with brain metastases of NSCLC. The data associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, due to dose limitation and the patient's organ tolerance, WBRT still has the risk of treatment failure or local recurrence [ 21 ]. In addition, WBRT can lead to irreversible neurological complications, which will affect patients' neurocognitive function, and has certain limitations [ 22 ]. In addition, local radiotherapy alone can achieve a high local control rate, but it cannot eliminate small metastases, and new brain metastases are easy to occur, with poor prognosis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to dose limitation and the patient's organ tolerance, WBRT still has the risk of treatment failure or local recurrence [ 21 ]. In addition, WBRT can lead to irreversible neurological complications, which will affect patients' neurocognitive function, and has certain limitations [ 22 ]. In addition, local radiotherapy alone can achieve a high local control rate, but it cannot eliminate small metastases, and new brain metastases are easy to occur, with poor prognosis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five clinical trials were included in the meta-analysis, which demonstrated that whole-brain radiation therapy plus temozolomide could significantly increase grade III-IV hematological and gastrointestinal toxicity in BMs of non-small-cell lung cancer, while significantly decreasing the objective response rate (ORR) compared to whole-brain radiation therapy alone (p = 0.05). 7 In the present case, the patient had previously experienced leukopenia and neutropenia after primary surgery and had a poor performance status (ECOG: 3). Therefore, the patient received temozolomide and bevacizumab in addition to radiotherapy.…”
Section: Discussionmentioning
confidence: 67%
“…Cisplatin and topotecan are the most common concomitant radiation chemotherapies for BMs; however, temozolomide, which could pass the blood–brain barrier and exhibit promising therapeutic effects in glioblastoma, may be a viable alternative. Twenty‐five clinical trials were included in the meta‐analysis, which demonstrated that whole‐brain radiation therapy plus temozolomide could significantly increase grade III‐IV hematological and gastrointestinal toxicity in BMs of non‐small‐cell lung cancer, while significantly decreasing the objective response rate (ORR) compared to whole‐brain radiation therapy alone ( p = 0.05) 7 …”
Section: Discussionmentioning
confidence: 99%
“…The same results were observed in NSCLC patients with BM, with significant improvement in objective response rate and progression-free survival (6.0 vs. 3.5 months; P=0.038) with the TMZ+WBRT group, though the differences in OS were not significant ( 42 ). With regard to combination therapy with TMZ plus irinotecan or TMZ plus WBRT for BM originating from NSCLC, TMZ may control microscopic central nervous system disease ( 43 , 44 ). Nevertheless, TMZ combined with immunotherapy for BM patients is seldom used ( 45 ).…”
Section: Discussionmentioning
confidence: 99%